Creative Thinking Skills at Public Senior High School 1 Belitang Oku Timur Regency South Sumatra - Sari, Tety Kartika; Al Muhdhar, Mimien Henie Irawati; Sueb, Sueb (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to measure the level of creative thinking skills among tenth-grade students at Public Senior High School 1 Belitang. Creative thinking skill is the ability to think in new, original, and flexible ways. It involves generating innovative ideas, solving problems in unique ways, and making connections between seemingly unrelated concepts. This skill is essential for adapting to new situations and fostering innovation across various disciplines. Creative thinking is one of the essential skills for the 21st century. This research employed a quantitative descriptive method with data collection through questionnaires and interviews. A total of 96 students participated in completing the questionnaires, and interviews were conducted with 3 biology teachers. The results showed that students’ average creative thinking skills were in the medium category, with a percentage of 70%. Interviews with teachers revealed that although teaching media such as PowerPoint and student worksheets were used, creative thinking skills were not explicitly taught or assessed. These findings highlight the importance of developing more innovative teaching methods and using technology and multimedia to enhance studentsâ€™ creative thinking skills.